2019
DOI: 10.1021/acssuschemeng.8b06841
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Carbonation-Activated Calcium Silicates as Sustainable Binders: Reactivity, Mechanical Performance, and Microstructure

Abstract: Calcium silicate minerals can react with CO2 to form calcium carbonate and have been proposed to be a sustainable binder as a potential CO2 sinker. In this study, the carbonation characteristics are comparatively assessed among calcium silicates having different calcium/silica (Ca/Si) ratios and polymorphs (CS, C3S2, γ-C2S, β-C2S, C3S). Calcium silicate compacts exposed to a 100% CO2 environment at a 0.4 MPa pressure were tested for carbonation temperature evolution, degree of carbonation (DOC), mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 38 publications
0
38
2
Order By: Relevance
“…The details about the materials preparation and testing procedures can be attained by consulting our previous study (Mu et al, 2018(Mu et al, , 2019.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The details about the materials preparation and testing procedures can be attained by consulting our previous study (Mu et al, 2018(Mu et al, , 2019.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, compared with the polymorph β-Ca 2 SiO 4 , γ-Ca 2 SiO 4 also showed much higher carbonation reactivity (Chang et al, 2016). Mu et al (2019) found that the γ-Ca 2 SiO 4 samples exposed to a 100% carbon dioxide environment under high pressure achieved mechanical properties in hours equivalent to that of the hydration product of a cement clinker hydrated for days, which provides a perspective of using carbonation-activated cementitious materials to reduce the dependence on alite-and belite-based cementitious materials. Theoretically, the use of γ-Ca 2 SiO 4 carbonation instead of cement clinker hydration not only reduces the carbon dioxide emissions from clinker production but also sequestrates the released carbon dioxide in a natural way, i.e., mineralization (Ashraf, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…1,5,9 The carbonated matrix is composed of continuous calcium carbonates encapsulating the isolated unreacted particles and the surrounding silica gels. 24,27 Mu et al assumed that the low porosity, abundant, and compact calcium carbonates are the essential traits of the high strength. 27 Depending on the distinguished physical and chemical properties required for different applications, the reaction pathway for the carbonation must be designed and optimized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24,27 Mu et al assumed that the low porosity, abundant, and compact calcium carbonates are the essential traits of the high strength. 27 Depending on the distinguished physical and chemical properties required for different applications, the reaction pathway for the carbonation must be designed and optimized. Therefore, the reaction mechanism and kinetics are worth to be investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cement production is an extensive energy consumption and high CO 2 emission industry, which accounts for about 5% of CO 2 emission and 12–15% energy consumption. Researchers have been working on new types of cementitious materials and low carbon materials to reduce their environmental impact. , A green energy-saving clinker containing lower C 3 S (≤50 wt %) content and higher C 4 AF (≥20 wt %) can calcinate at a lower sintering temperature in comparison with that of Portland cement, which is called high ferrite cement (HFC), and it can reduce effectively the energy consumption and emissions in clinker production, possessing a wide range of application prospects.…”
Section: Introductionmentioning
confidence: 99%